Problematic Wildlife II 2020
DOI: 10.1007/978-3-030-42335-3_18
|View full text |Cite
|
Sign up to set email alerts
|

Snakes, Snakebites, and Humans

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…In this study, we also found that the majority of King Cobras were killed during daytime, which likely reflects the diurnal nature of both humans and King Cobras (Shankar et al 2013). Although some Hindus and Buddhists have deep-rooted traditional, cultural, and religious beliefs involving snakes, and the worship of snakes (i.e., "ophiolatry") as gods (Shah and Tiwari 2004;Perry et al 2020), we found that most people kill snakes when encountered whether the snake is venomous or not. For example, we found that people readily killed non-venomous species, such as pythons (Python spp.…”
Section: Resultsmentioning
confidence: 69%
“…In this study, we also found that the majority of King Cobras were killed during daytime, which likely reflects the diurnal nature of both humans and King Cobras (Shankar et al 2013). Although some Hindus and Buddhists have deep-rooted traditional, cultural, and religious beliefs involving snakes, and the worship of snakes (i.e., "ophiolatry") as gods (Shah and Tiwari 2004;Perry et al 2020), we found that most people kill snakes when encountered whether the snake is venomous or not. For example, we found that people readily killed non-venomous species, such as pythons (Python spp.…”
Section: Resultsmentioning
confidence: 69%
“…For this reason, snakebites tend to be concentrated in peri-urban and rural settings ( Gutiérrez et al, 2010 ; Minghui et al, 2019 ). Likewise, urban parks are frequent sources of snakebites, as these provide refugia for animal species in human-dominated landscapes ( Parkin et al, 2020 ; Perry et al, 2020 ; Soga and Gaston, 2020 ). Although the effect of land use change on snakebite is highly variable between regions, it can be explained by the composition of snake assemblages and their local population sizes ( Oliveira et al, 2020 ).…”
Section: Eco-epidemiology Of Snakebitesmentioning
confidence: 99%
“…Prevention in the first place will improve prosperity by decreasing life years of disability ( Hotez et al, 2016 ; 2014 ; Warrell, 2010 ) and ease nature conservation by reducing snake-human conflicts and the persecution of venomous snakes ( Fita et al, 2010 ; Means, 2009 ; Pandey et al, 2016 ), reduce the burden on public health services and improve safety standards in food production ( Warrell, 2010 ). In order to prevent conflicts among SDGs snakebite prevention should encompass the different levels of ecological organization summarized above, ranging from strategic management of the forest-agricultural frontier and urban sprawl ( Perry et al, 2020 ), education, adequate collection of snakebite statistics to monitor their response to environmental changes and conservation policies, to developing and optimizing the delivery of effective antivenoms and personal protective equipment ( Gutiérrez et al, 2010 ; Longbottom et al, 2018 ).…”
Section: Eco-epidemiology Of Snakebitesmentioning
confidence: 99%
“…Addled by alcohol and other chemicals, she wanders the grounds at night, thus meeting her fate. And yes, this can happen (Perry et al 2020), although it never has in the United States.…”
Section: Reptiles and Amphibians C O N S E R V At I O N A N D N At U R A L H I S T O R Ymentioning
confidence: 99%